The Multiplicity of Meanings in Cognitive and Semantic Perspectives - Dalieva Madina (Scientific Trends, 2024)
This article examines polysemy, a phenomenon where words have multiple related meanings, across various languages including English, Russian, Uzbek, and Tajik. It synthesizes views from scholars like T. Georgakopoulos, Grinev-Griniewich, and R. Carston, emphasizing cognitive, semantic, and pragmatic aspects of polysemy. The research explores how polysemy complicates the mental lexicon, necessitates contextual disambiguation, and is influenced by cultural and structural language differences. It discusses the challenges of representing polysemous words in dictionaries, their implications for language learning, and the hurdles they present in natural language processing. The article also highlights the importance of understanding rule-based and resemblance-based polysemy, and the role of pragmatic inference in interpreting meanings. This comprehensive analysis of polysemy underscores its significance in understanding cognitive processes, language evolution, and cultural diversity.
Keywords: Polysemy, cognitive linguistics, semantic derivation, pragmatic inference, language processing, lexical semantics, cross-linguistic comparison.